Product lambda-doublet ratios as an imprint of chemical reaction mechanism - Jambrina, P; Zanchet, A; Aldegunde, J; Brouard, M; Aoiz, F (Nature Publishing Group, 2016)
In the last decade, the development of theoretical methods has allowed chemists to reproduce and explain almost all of the experimental data associated with elementary atom plus diatom collisions. However, there are still a few examples where theory cannot account yet for experimental results. This is the case for the preferential population of one of the Λ-doublet states produced by chemical reactions. In particular, recent measurements of the OD((2)Π) product of the O((3)P)+D2 reaction have shown a clear preference for the Π(A') Λ-doublet states, in apparent contradiction with ab initio calculations, which predict a larger reactivity on the A'' potential energy surface. Here we present a method to calculate the Λ-doublet ratio when concurrent potential energy surfaces participate in the reaction. It accounts for the experimental Λ-doublet populations via explicit consideration of the stereodynamics of the process. Furthermore, our results demonstrate that the propensity of the Π(A') state is a consequence of the different mechanisms of the reaction on the two concurrent potential energy surfaces.